Potential role of climate change on the spread of salmonid skin condition: the biogeochemical hypothesis on ulcerative dermal necrosis on the Słupia River - Poland - Stokowski, Marcin; Sobiegraj, Wojciech; Kulczykowska, Ewa (Frontiers in Marine Science, 2023)
Ulcerative dermal necrosis (UDN) it is an idiopathic condition of fish skin that has been reported in Europe since 1820. UDN affects primarily an epidermal and dermal layer of the skin lesion, which in the early stages, occurs in the head area of migratory adult salmonids entering freshwater for upstream river migration. Studies show that acid-base water properties in estuaries are exceptionally dynamic, which results from the variability of the CO2 system. The carbonate system is shaped by the net effect of mineralization and primary production enhanced by: i) the constant inflow of nutrients and organic matter from the land and ii) the horizontal and vertical mixing of the two end-members of the total alkalinity, dissolved organic carbon and pCO2; both cause high acid-base gradients between the river and the ocean. Climate change affects the biogeochemical characteristics of estuaries. We show a strong positive correlation between local temperature anomalies along the Polish coast and the occurrence of UDN in Salmo trutta sp. spawners in the Słupia River, Poland. The results suggest that the biogeochemical processes associated with climate change may be at least one component of the UDN aetiology. They also highlight the need for systematic monitoring to understand these processes and their consequences. It is crucial for restoring and further preserving sustainability in the coastal system, which involves marine life and human well-being. Furthermore, salmonids are valuable commercial fish. Thus any health issues may have a profound effect on fisheries, local communities and the fish market in general.